Effect of Al content on the critical resolved shear stress for twin nucleation and growth in Mg alloys. (15th April 2020) - Wang, Jingya; Molina-Aldareguía, Jon M.; LLorca, Javier
Abstract: The effect of Al atoms in solid solution on the critical resolved shear stress for twin nucleation and growth was analyzed by means of the combination of diffusion couples with compression tests in micropillars oriented for twinning. The critical resolved shear stress for twin nucleation was higher than that for twin growth and both increased by the same amount with the Al content. Nevertheless, the increase was small (≈ 10 MPa) for 4 at%Al but large (up to 60–70 MPa) for 9 at%Al. These results were in agreement with Labusch-models based on first principles calculations in the dilute regime (< 5 at%Al). Comparison with recent data in the literature showed that Al atoms are more effective in increasing the critical resolved shear stresses for twin nucleation and growth than for basal slip. Finally, compression tests in micropillars oriented along [0001] showed the critical shear stress for pyramidal slip increased rapidly with the Al content from 98 MPa in pure Mg to 250 MPa in Mg-9 at%Al. Overall, the presence of Al atoms decreased slightly the plastic anisotropy of Mg (understood as the critical resolved shear stress ratios between non-basal and basal plastic deformation mechanisms). Graphical abstract: Image, graphical abstract